Assessing motor competence in Indonesian sports science admissions: A comparison of portfolio assessment and direct practical testing - Ngadiman; Akbar Kusuma Abadi; Eko Sumianto; Agung Prabowo; Bayu Suko Wahono (Jurnal Cakrawala Pendidikan, 2026)
Indonesia’s National Selection for State University Admission (SNMPTN) for Sports Science programs has shifted from practical motor skill tests to portfolio-based assessment, raising concerns about validity and reliability in measuring motor competence. This study examined the validity and reliability of portfolio assessment by comparing it with direct motor skill tests as the criterion measure. A quantitative descriptive-verificative design involved 50 Physical Education students at Jenderal Soedirman University with complete portfolio and practical test data. Four motor skill domains were assessed: hand-eye coordination, agility, lower-limb muscle power, and endurance. Statistical analyses included Wilcoxon test, Spearman’s correlation, Intraclass Correlation Coefficient (ICC), Bland-Altman analysis, and error measurements. Results showed portfolio scores consistently overestimated performance with significant differences in three domains (p ≤ 0.001). Spearman’s correlations ranged from moderate to strong (ρ = 0.432–0.814), yet ICC values indicated low-to-moderate absolute agreement except for lower-limb muscle power (ICC = 0.800). Bland-Altman analysis revealed systematic positive bias with wide limits of agreement. These findings suggest portfolio assessment is inadequate as a standalone instrument for selecting candidates based on motor skills and should serve as a complementary tool to standardize direct practical tests in Sports Science admissions.